Practical sensor fault tolerant control system - Yang, S.S.; Mid, E.C.; Mohamed, H.A.F.; Moghavvemi, M. (2008)
The fundamental purpose of an FTCS scheme is to ensure that faults do not result in system failure and ensure the achievement of best performance at a lower degree of system performance. In this paper we propose a fault tolerant control design consisting of two parts: a nominal performance controller and a fault detection element to provide fault compensating signals to the feedback loop. The nominal controller can have any given structure that satisfies the performance specification. When a sensor failure is detected, the controller structure is augmented by signals from plant model to compensate for the fault. A temperature control system is used as a case study. Results of simulation and real time implementation for temperature control system concur and demonstrate the applicability of the proposed FTCS scheme.